The Impact of COVID-19 on Sentencing Practices - Zvonkovich, Jordan (American journal of criminal justice, 2023)
The COVID-19 pandemic significantly impacted court operations across the country. In March and April of 2020 "business-as-usual" was upended and the entire court system was forced to respond in an unprecedented way. Using Pennsylvania Commission on Sentencing data, we explore the impact that COVID-19 had on sentencing outcomes. Three distinct periods: pre-COVID-19, the onset of COVID-19 during which an emergency judicial order limited court operations, and a period after the order was lifted are defined to compare trends and assess differences. Utilizing the natural experiment created by the pandemic we present a descriptive and multivariate analysis of sentencing practices focused on racial disparities. The paper employs two theoretical frameworks (focal concerns and the liberation hypothesis) to motivate competing expectations regarding sentencing behavior and disparities.